Avaliação da aprendizagem centrada no desenvolvimento das competências prescritas na BNCC: o caso de uma escola pública de ensino médio em Sobral – CE - Nascimento, Francisco Cartegiano de Araujo (2023)
The assessment of school learning is increasingly a concern for educators, parents and students and has become the object of interest of public educational policies with regard to the production of teaching materials, teacher training, infrastructure, teaching strategies, curriculum organization and, above all, large-scale results, focusing on the management of education networks. It is, therefore, a complex subject, the discussion of which has gained ground among scholars, especially in the last three decades. Theoretically, the assessment of learning that takes place in the classroom, especially involving the student and teacher, is developed with the aim of allowing the student to be monitored, thus enabling decisions to be made to review and resize pedagogical practices in the teaching-learning process. However, evaluation processes are not neutral, since they are influenced by the school's pedagogical objectives, i.e. they are an action that is affected by political forces and has political effects. In this context, this investigation aims to understand how the concept of learning assessment, centered on the development of competencies prescribed in the National Common Curriculum Base (BNCC), will be reflected in the education of students in the New High School. We started with the following problem: will learning assessment geared towards the development of the competences listed in the BNCC contribute to an integral education that focuses on the multiple human dimensions (cognitive, intellectual, scientific, ethical, aesthetic, affective, social), or will it be more aligned with motivating and training young people to meet the demands of the future roles they will play in the job market? The methodological path adopted corresponds to a qualitative investigation, of a descritive nature and a case study method, using bibliographic research, document analysis, semi-structured interviews and participant observation as data collection techniques. The results indicate that assessment in the context of the BNCC needs to be an integral part of the teaching and learning processes, taking on a formative character. They point out that the training project based on the development of competences is more aligned with the expectations of external assessments and preparation for the job market, to the detriment of the students' comprehensive training. They also reveal that the assessment of learning centered on the ten competences of the BNCC, within the scope of the New High School, is basically based on two purposes: on the one hand, as a pedagogical and formative resource with a view to student learning and development, and on the other, as a managerial and control mechanism.